JNSR 2021
DOI: 10.7176/jnsr/12-12-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two contrasting cassava canopy structures on weed flora composition in a rainforest zone of Nigeria.

Abstract: The impact of weed competition on crop growth is a universal concern to farmers. This study was conducted in 2010 at the Teaching and Research Farm, Obafemi Awolowo University, Ile-Ife to evaluate the impact of cassava canopy on weed diversity and identify shade-tolerant weed species in response to varying canopy structure at Obafemi Awolowo University Teaching and Research Farm, Ile-Ife ecological zone. The treatments consist of hand-weeded, herbicidal treatment, and unweeded checks in the main plot. The sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The current results (Table 3) support our hypothesis that canopy cover reduces weed-competitiveness as observed in the branching (Chila) and semi-branching (Nalumino) varieties. The current results are corroborated by the work of Ola et al (2021a) who reported higher cassava root yields emanating from 20% weed suppression from a variety with a broad canopy structure. A similar weed smothering effect from branching cassava varieties on weeds was also reported by Temitope (2012) from studies conducted in Nigeria.…”
Section: Cassava Canopy Smothering Effect On Weedssupporting
confidence: 87%
See 2 more Smart Citations
“…The current results (Table 3) support our hypothesis that canopy cover reduces weed-competitiveness as observed in the branching (Chila) and semi-branching (Nalumino) varieties. The current results are corroborated by the work of Ola et al (2021a) who reported higher cassava root yields emanating from 20% weed suppression from a variety with a broad canopy structure. A similar weed smothering effect from branching cassava varieties on weeds was also reported by Temitope (2012) from studies conducted in Nigeria.…”
Section: Cassava Canopy Smothering Effect On Weedssupporting
confidence: 87%
“…Cassava canopy structure has been widely reported to affect both the weed population and the diversity annual weed species which grow in cassava plots. Therefore, the branching and broad canopy structure is an important attribute that determines weed competitiveness in sole and intercropping systems (Ola et al, 2021a;Weerarathne et al, 2017). In experiments where weeds were left to freely infest cassava fields, there is evidence that reduced yield losses were observed in plots where branching plant type was grown (40%) compared to root yield losses of non-branching cassava varieties (Akobundu, 1980).…”
Section: Cassava Canopy Smothering Effect On Weedsmentioning
confidence: 99%
See 1 more Smart Citation